Multicenter Experience of Surgical Explantation of Carotid Stents for Recurrent Stenosis. (November 2016) - Columbo, Jesse A.; McCallum, John C.; Goodney, Philip P.; Bower, Thomas C.; Schermerhorn, Marc L.; Powell, Richard J.; DeMartino, Randall R.
Objective: A significant cohort of patients who have undergone carotid artery stenting (CAS) will have in-stent restenosis (ISR). The optimal management of symptomatic or severe ISR remains poorly defined. The purpose of this study was to describe the indications, treatment, and mid- to long-term outcomes of patients undergoing CAS explantation for ISR. Methods: All patients undergoing internal carotid artery stent explantation with carotid artery reconstruction at Mayo Clinic Rochester, Dartmouth-Hitchcock Medical Center, and Beth-Israel Deaconess Medical Center from 2003 to 2013 were retrospectively reviewed. Isolated common carotid artery stents were excluded. Demographics, comorbidities, indications for explantation, operative details, and perioperative and postoperative outcomes were reviewed. Results: Over the study interval, a total of 971 patients underwent carotid stenting across the 3 centers. Of these, 8 patients ultimately underwent CAS explantation with carotid artery reconstruction. Mean age was 69 years and 5 patients were male. Index stent placement was for symptomatic stenosis in 4 patients, asymptomatic restenosis after endarterectomy in 2 patients, asymptomatic high lesion in 1 patient, and asymptomatic critical stenosis in 1 patient. Indications for explantation were symptomatic ISR in 4 patients and asymptomatic severe ISR in 4 patients. Method of repair was stent explantation and patch angioplasty in 5 and en bloc carotid resection with bypass in 3 patients. There were no perioperative neurologic events or cranial nerve injuries. At a mean follow-up of 38.7 months, there were 2 late disabling ipsilateral strokes (14.4 months and 19.1 months). Conclusion: A significant cohort of patients who have undergone CAS will have ISR. Although excellent perioperative results after surgical explantation can be obtained, this patient subgroup remains at risk for late neurologic events. Appropriate patient selection and diligent long-term follow-up are mandated to obtain optimal outcomes.